Initial-boundary Value Problems to the One-dimensional Compressible Navier- Stokes-Poisson system with Large Amplitude - Wang, Li; Jin, Lei (Journal of Applied Nonlinear Dynamics, 2026)
Magnetic fluid is a new type of functional material. The motion of com-pressible, viscous self-gravitating fluids can be expressed by Navier-Stokes-Poisson equations. This study demonstrates the global, non-vacuum solutions with large amplitude to the initialboundary value problem of the one-dimensional compressible Navier- Stokes-Poisson system with degenerate dependent viscosity coefficients and density and temperature dependent heat conductivity coefficients. The main constituent of the detail analysis is to derive the positive lower and upper bounds on the specific volume and the absolute temperature.